Mosaics, empresses and other things in Byzantium - James, Liz, author.
1 online resource.
Keywords: "This volume consists of 15 articles published between 1991 and 2018. It falls into three sections, reflecting different areas of Liz James's interests. The first section is light and colour and mosaics, where four articles considering light and colour in mosaics and the making of mosaics, as well as the question of what it means to define mosaics as 'Byzantine' are reprinted. The second brings together four pieces on empresses: their relationships with female personifications and the Mother of God, their roles in founding and refounding buildings, and their employment as ciphers by some authors. Finally, seven papers cover a range of topics what monumental images of saints in churches might have been for; what the differences between relics and icons might have been; how captions to images can be misleading; why touch was an important sense; how words can sometimes 'just' be decorative rather than for reading; why the materiality of objects makes a difference. There is also a brief section of additional notes and comments which add to, update and reflect on each piece now in 2024. Mosaics, Empresses and Other Things in Byzantium will be of interest to scholars and students alike interested in material culture, the depiction of regal women, and the use of relics and icons in the Byzantine Empire"--